Rancang Bangun Alat Pirolisis Tabung Bertingkat Pengolah Sampah Plastik menjadi BBM Alternatif (PITARA) - Arif Surono; Wachid Yahya; Onery Andy Saputra; Muhammad Iwan (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Plastic waste is difficult to decompose and continues to create environmental pressure, while the need for alternative liquid fuels remains high. This study aimed to design and test PITARA, a multi-stage tube pyrolysis prototype for converting mixed plastic waste into liquid fuel. The method used an experimental engineering design through functional analysis, structural design, fabrication, functional testing, performance testing, and preliminary fuel-property testing. The unit consisted of a 10 kg stainless-steel reactor, a dual-fuel burner using LPG and charcoal, and a vertical double-pipe condenser. The feedstock consisted of mixed PP, PE, HDPE, and similar plastics processed into 2 x 3 mm pellets. From 10 kg of clean and dry plastic waste, the prototype produced 10.35 L of liquid condensate, equivalent to 8.221 kg or 82.21% by mass, about 2 g of solid residue, and an estimated 17.77% gaseous or non-condensable fraction by difference. Laboratory testing showed a density of 0.7944 g/cm³, viscosity of 0.257 cP, calorific value of 37.37 MJ/kg, and positive flammability. The novelty of this study lies in the integration of a dual-fuel burner, compact stainless-steel reactor, and vertical double-pipe condenser for small-scale mixed-plastic pyrolysis. The findings represent preliminary prototype validation; further GC-MS analysis, fuel-standard testing, emission testing, and engine performance evaluation are required.